Problematika Sistem Presidential Threshold Ditinjau dari Maqāṣid al-Syarī’ah - Jamrud Zaman; Kasuwi Saiban (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The presidential threshold is a threshold requirement for a political party or a coalition of political parties supporting a presidential and vice-presidential candidate pair using the percentage of the DPR seat acquisition or the national valid vote acquisition in the DPR general election. The presence of this presidential threshold is a barrier to the right to equal opportunity in government. This research aims to evaluate the various rights that have been violated by the presidential threshold policy from the perspective of human rights and maqashid sharia as a new view of the efforts to reform a just law. This research includes normative research with statutory and legal policy approaches. The results and discussion of this research are that the general election law related to the presidential threshold has been tested by the Constitutional Court. However, the Court always rejects the application because it is of the opinion that the presidential threshold is an open authority of the legislator based on the delegation of Article 6A Paragraph (5) of the 1945 Constitution. The rejection resulted in disappointment for the Indonesian people because it was considered to limit the right to become a leader. In the perspective of Maqāṣid syarī'ah, the presidential threshold policy has also violated hifdzu 'aql. Therefore, in the future, fair legal reform efforts must be realized, namely by amending Article 6A Paragraph (2) related to presidential requirements to clearly regulate and close the loopholes of interpretation by the legislators and moral development of constitutional judges so that they really fight for the rights of citizens with a further view of the constitution.